Ischemia Reperfusion Injury Triggers CXCL13 Release and B-Cell Recruitment After Allogenic Kidney Transplantation - Kreimann, Kirill; Jang, Mi-Sun; Rong, Song; Greite, Robert; von Vietinghoff, Sibylle; Schmitt, Roland; Bräsen, Jan Hinrich; Schiffer, Lena; Gerstenberg, Jessica; Vijayan, Vijith; Dittrich-Breiholz, Oliver; Wang, Li; et al. (Frontiers in Immunology, 2020)
Ischemia reperfusion injury (IRI) is linked with inflammation in kidney transplantation (ktx). The chemokine CXCL13, also known as B lymphocyte chemoattractant, mediates recruitment of B cells within follicles of lymphoid tissues and has recently been identified as a systemic biomarker for acute kidney allograft rejection. The goal of this study was to explore whether IRI contributes to the increase in the levels of systemic CXCL13 observed in ktx. It is demonstrated that systemic levels of CXCL13 were increased in mouse models of uni- and bilateral renal IRI, which correlated with the duration of IRI. Moreover, in unilateral renal IRI an increase in CXCL13 mRNA expression in ischemic kidneys was also observed. Furthermore, immunohistochemistry revealed an infiltration of CD22+ve B-cells in the ischemic kidneys 7 days post IRI. Subsequent, single-cell RNA sequencing analysis indicated an increase in the number of cells expressing the CXCL13 receptor CXCR5, the majority of which were B-cells. The potential relevance of these findings was further evaluated in a mouse model of ktx. Increased levels of systemic serum CXCL13 correlated with length of cold ischemia time and were further amplified by transplantation of allogenic kidneys in comparison to isogenic kidneys. Taken together, our findings indicate that IRI is associated with increased systemic levels of CXCL13 in renal IRI and ktx.